Nicanor y la Violeta : A Critical Analysis of the Use of the Definite Article Before Male and Female Proper Nouns [ Nicanor y la Violeta : Un Análisis Crítico del Uso del Artículo Definido Ante Nombres Propios Masculinos y Femeninos] - Roman-Montes de Oca, D; Aliaga-Rovira, L (Universidad de la Serena,Departamento de Artes y Letras, 2020)
This article studies the structure “definite article + proper noun anthroponym”anditsdistributionofuseincasesoffemaleandmaleanthroponyms. It is assumed that this structure is more frequent when the anthroponym is female (“la Violeta” and not “el Nicanor”). Since the presence of the article is expletive before proper nouns and, on the contrary, the use of this determinant or another is required, in specific syntactic positions, before common nouns, the appearance of the definite article preceding the feminine anthroponym could be a mark of social prejudice towards woman. To corroborate this hypothesis, the phenomenon studied was tracked in chilean written press texts, in order to analysing its appearance and frequency of use in cases of feminine and masculine anthroponyms. © Este trabajo se encuentra bajo la licencia Creative Commons Attribution 3.0.